Efforts To Improve The Learning Outcomes Of Indonesian Of 7th Grade Students In SMPN 9 Sorong Through The Implementation Of The Cooperative Model Integrated Reading And Composition - Sabring L, Muh. (Sains Global Institut, 2019)
This research is a classroom action research using a qualitative description analysis that aims to determine whether there is an influence of the application of the CIRC type cooperative learning model in an effort to improve student learning outcomes. The subjects in this study were students of class VII-3, SMPN 9 Sorong whose average learning achievement was lower than other class VII, with a total of 26 students. The procedure of the study was to choose a learning model that was assessed according to the material presented. The PTK procedure consists of 2 cycles with 3 meetings per cycle, according to the level of the problem to be solved and the conditions to be improved. Each cycle consists of four stages as follows: 1) planning; 2) implementing actions; 3) observation and evaluation of actions; and 4) reflection of actions. Data in this study were collected through observation and tests to find out the extent of students' mastery learning towards the material delivered using the CIRC type of cooperative learning model. The results of the study show that: (1) In using the CIRC type of cooperative learning model the teacher must also pay attention to the importance of classroom management. This is for the sake of the smooth learning process; (2) The average score of students' understanding in paying attention to problems about determining the main ideas and problems in arlikel through intense reading activities, in the first cycle of 54.8, in the second cycle increased by 69.2, while in the third cycle increased by 83, 5 is quite good. Likewise, the completion of learning in cycle I by 57.6% increased in cycle III to 65.3% and also increased in cycle III to 100%; (3) CIRC type of cooperative learning model can improve student learning outcomes and can improve students' ability to solve problems regarding basic competencies in understanding explanatory text through oral and written on Indonesian subjects in VII grade students of SMPN 9 Sorong.